2005
DOI: 10.1111/j.1365-2265.2005.02401.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of an Italian papillary thyroid carcinoma cohort revealed high prevalence of BRAF mutations, absence of RAS mutations and allowed the detection of a new mutation of BRAF oncoprotein (BRAFV599Ins)

Abstract: These data indicate that BRAF mutations are the most frequent genetic event in PTC and that RAS mutations, besides being a genetic hallmark of follicular tumours, are rare or completely absent in PTC from our area. Together, BRAF mutations and rarer RET rearrangements accounted for a genetic event in two-thirds of PTCs. This study showed a novel and presumably oncogenic mutation of BRAF, which is BRAF(V599Ins).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 27 publications
1
40
1
3
Order By: Relevance
“…32 Activating mutations of all three RAS oncogenes (KRAS, HRAS and NRAS) have historically been associated with a higher frequency in follicular than in papillary tumours. 33,34 A recent study by Carta et al 35 found an absence of RAS mutations in an Italian papillary thyroid carcinoma cohort but the presence of RAS oncogenic mutations in 75% of follicular thyroid carcinomas.…”
Section: Expression Patternsmentioning
confidence: 97%
“…32 Activating mutations of all three RAS oncogenes (KRAS, HRAS and NRAS) have historically been associated with a higher frequency in follicular than in papillary tumours. 33,34 A recent study by Carta et al 35 found an absence of RAS mutations in an Italian papillary thyroid carcinoma cohort but the presence of RAS oncogenic mutations in 75% of follicular thyroid carcinomas.…”
Section: Expression Patternsmentioning
confidence: 97%
“…Approximately 95% of all BRAF mutations involve a T>A transversion at gene position 1799, resulting in valine to glutamate amino acid substitution at position 600 of the protein (V600E). Other described alterations in the BRAF gene include the A>G transversion at gene position 1801 (K601E), fusion with the A-kinase anchor protein 9 (AKAP9) gene and small in-frame insertions or deletions around codon 600 (24)(25)(26).…”
Section: Papillary Thyroid Carcinomamentioning
confidence: 99%
“…12,14 Other and rare mechanisms of BRAF activation in papillary thyroid cancer include K601E point mutation, small in-frame insertions or deletions surrounding codon 600, [15][16][17] and AKAP9-BRAF rearrangement, which is more common in papillary carcinomas associated with radiation exposure. 18 In addition to papillary carcinomas, BRAF is found mutated in thyroid anaplastic and poorly differentiated carcinomas, typically in those tumors that also contain areas of well-differentiated papillary carcinoma.…”
Section: Brafmentioning
confidence: 99%